Alternative Lengthening of Telomeres in Pediatric Cancer: Mechanisms to Therapies - Kent, Thomas; Gracias, Deanne; Shepherd, Samuel; Clynes, David (Frontiers in Oncology, 2020)
Achieving replicative immortality is a crucial step in tumorigenesis and requires both bypassing cell cycle checkpoints and the extension of telomeres, sequences that protect the distal ends of chromosomes during replication. In the majority of cancers this is achieved through the enzyme telomerase, however a subset of cancers instead utilise a telomerase-independent mechanism of telomere elongation – the Alternative Lengthening of Telomeres (ALT) pathway. Recent work has aimed to decipher the exact mechanism that underlies this pathway. To this end, this pathway has now been shown to extend telomeres through exploitation of DNA repair machinery in a unique process that may present a number of druggable targets. The identification of such targets, and the subsequent development or repurposing of therapies to these targets may be crucial to improving the prognosis for many ALT-positive cancers, wherein mean survival is lower than non-ALT counterparts and the cancers themselves are particularly unresponsive to standard of care therapies. In this review we summarise the recent identification of many aspects of the ALT pathway, and the therapies that may be employed to exploit these new targets.